A Mixed-Integer Linear Programming Model for the Optimal Operation and Design of Residential Neighbourhoods. Issue 1 (2019) - Dorneanu, Bogdan; Sidnell, Tim; Clarke, Fiona; Mechleri, Evgenia; Arellano-Garcia, Harvey
Abstract: This paper presents the results of a Mixed-Integer Liner Programming (MILP) model for the optimal design and operation of a distributed energy resource (DER) system in the UK residential sector. The model optimizes the design and utilization of a network with integrated heating/cooling pipelines and micro-grid connections between neighborhoods, in two case studies of five and ten houses, respectively. This work explores the use of feed-in tariffs, renewable heat incentives and the ability to buy and sell from and to the national grid. Depending on the scenario it is shown that DER networks mitigate around 30-40% of the CO2 emissions per household, compared with 'traditional generation', in which all the electricity comes from the national grid, the heating and domestic hot water are provided by gas boilers and air-conditioning units provide space cooling. Moreover, money from feed-in tariffs, renewable heat incentives and sales to the grid, as well as reduced grid purchases, make the DER networks more economical, and more profitable (approximately £100 per year per household), compared with the traditional energy system.